Gravely Pregnant with Freireian Alternativity: Can Foreign Language Learning Avoid Reinforcing Cultural and Social Hegemony? - Sidney Pratt (Asociación Colombiana de Profesores de Ingles, 2016)
In this paper, I will discuss the experiences of a group of teachers in producing foreign language material, in this case English, for use in classes attended by young adult school dropouts. I will contrast hegemonic and liberatory pedagogies and reflect on their potential for closing down or opening up the potential of learners to take their part in the transformation of the world. I will provide examples of why foreign language learning and use is intrinsically hegemonic and how we have tried to counter this in the material we have produced. I will attempt to demonstrate what Freire's inédito viável, roughly translated into English as untested hypothesis, looks like in our practice. I will describe some problems we have not been able to solve to our satisfaction. Finally I will reflect on this question: If young adult school dropouts cannot manage their own language well, why learn a foreign language?